Perifascial areolar tissue graft promotes angiogenesis and wound healing in an exposed ischemic component rabbit model. - Toru Miyanaga; Yasuo Yoshitomi; Aiko Miyanaga (PLoS ONE, 2024)
Multiple studies have reported the use of perifascial areolar tissue (PAT) grafts to treat wounds involving exposed ischemic tissues, avascular structures, and defective membrane structures. Our objective was to assess the quantitative effects of PAT grafts and their suitability for wounds with ischemic tissue exposure and to qualitatively determine the factors through which PAT promotes wound healing and repair. We conducted histological, immunohistochemical, and mass spectrometric analyses of the PAT grafts. PAT grafts contain numerous CD34+ progenitor/stem cells, extracellular matrix, growth factors, and cytokines that promote wound healing and angiogenesis. Furthermore, we established a male rabbit model to compare the efficacy of PAT grafting with that of an occlusive dressing treatment (control) for wounds with cartilage exposure. PAT grafts could cover ischemic components with granulation tissue and promote angiogenesis. Macroscopic and histological observations of the PAT graft on postoperative day seven revealed capillaries bridging the ischemic tissue (vascular bridging). Additionally, the PAT graft suppressed wound contraction and alpha smooth muscle actin (αSMA) levels and promoted epithelialization. These findings suggested that PAT can serve as a platform to enhance wound healing and promote angiogenesis. This is the first study to quantify the therapeutic efficacy of PAT grafts, revealing their high value for the treatment of wounds involving exposed ischemic structures. The effectiveness of PAT grafts can be attributed to two primary factors: vascular bridging and the provision of three essential elements (progenitor/stem cells, extracellular matrix molecules, and growth factors/cytokines). Moreover, PAT grafts may be used as transplant materials to mitigate excessive wound contraction and the development of hypertrophic scarring.